Implementasi Metode SAW Untuk Perangkingan Siswa Dalam Sistem Informasi Akademik Di SMPIT Cordova Pondok Aren - Imam Balda; Devi Damayanti; Fajar Agung Nugroho (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Rapid technological developments in the era of globalization encourage educational institutions to adopt computer technology to accelerate and improve the accuracy of academic data management. At SMPIT Cordova Pondok Aren, academic data management is still done manually, causing various problems such as difficulties in searching for student data, compiling academic reports, and determining unfair student rankings because they are only based on final grades. This study aims to develop a computer-based system that can improve academic data management at SMPIT Cordova Pondok Aren by overcoming these problems and providing a fairer student ranking process using the SAW (Simple Additive Weighting) method. The development method used is Waterfall, with data collection through observation and interviews, then analyzed using the SAW method to determine student rankings based on predetermined value weights and criteria. The results of testing conducted on 15 students in Class VIII1 showed that Shoffa Nur Aisyah achieved a score of 0.996853, making her one of the students with the highest ranking. In addition, a survey conducted on 30 respondents showed that 87.33% gave the answer "Strongly Agree" to the implementation of this system, This signals widespread support for the system's benefits in improving academic data management and student ranking.